2015
DOI: 10.1016/j.socscimed.2015.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Communal bereavement and resilience in the aftermath of a terrorist event: Evidence from a natural experiment

Abstract: Rationale Sociological analyses of the psychological distress experienced by persons indirectly exposed to traumatic stressors have been conceptualized as a form of communal bereavement, defined by Catalano and Hartig (2001) as the experience of distress among persons not attached to the deceased. Their theory predicts communal bereavement responses particularly in the setting of loss of essential state, religious, or economic institutions. Objective To estimate the extent to which the September 11, 2001 att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 69 publications
2
32
0
Order By: Relevance
“…The loneliness and worry coefficients are over one half of a standard deviation in Europe, but lower in the US. These can be compared to the estimated standarddeviation effect of 9/11 on mental health of 0.1 to 0.3 (Tsai and Venkataramani (2015)) and depression of 0.5 (Knudsen et al (2005)) in the US, and an effect on psychological well-being in the UK of 0.07 (Metcalfe et al (2011)). The Boston Bombing had an estimated effect on happiness and net affect of one-third of a standard deviation (Clark et al (Forthcoming)).…”
Section: Differences-in-differences Estimation Resultsmentioning
confidence: 99%
“…The loneliness and worry coefficients are over one half of a standard deviation in Europe, but lower in the US. These can be compared to the estimated standarddeviation effect of 9/11 on mental health of 0.1 to 0.3 (Tsai and Venkataramani (2015)) and depression of 0.5 (Knudsen et al (2005)) in the US, and an effect on psychological well-being in the UK of 0.07 (Metcalfe et al (2011)). The Boston Bombing had an estimated effect on happiness and net affect of one-third of a standard deviation (Clark et al (Forthcoming)).…”
Section: Differences-in-differences Estimation Resultsmentioning
confidence: 99%
“…Therefore the following four sensitivity analyses were done (New York, California, California & New York, and the entire US) to determine if the overall pooled OR would change. Research has shown that the 9/11 attacks caused transient psychological distress in the whole of the US, but this distress was greatest in the New York City area (16). Informed by this fact, we chose New York for the final sensitivity analysis so as to capture the presumed maximum effect of the attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although we used different statistical techniques, our findings are in agreement with the primary studies. Furthermore, a recent study (16) revealed that population level psychological distress following the 9/11 attacks lasted for about one month and then resolved. A similar pattern was observed with the sex ratio at birth after 9/11 albeit with the expected lag, from the time of miscarriage/stillbirth to when live birth would have occurred.…”
Section: Meta-analysismentioning
confidence: 99%
“…Three recent contributions that are methodologically and topically related to my study are Tsai and Venkataramani (2015), Kim and Kim (2018), and Clark et al . (2020), who all also use a residency‐based measure of terrorism exposure and a differences‐in‐differences approach.…”
Section: Introductionmentioning
confidence: 91%